(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Traditionally, the Indian tax authorities relied heavily on indirect taxes. Indirect tax revenue was a major source of tax revenue until tax reforms were made during the nineties. The main issue presented with a strong reliance on indirect taxes was that the majority of Indians were poor and therefore the growing base of direct taxation had its natural limits. But India’s indirect tax system is characterized by tax evasion in the production of goods and services that leads to disruption of productivity and slower economic growth. There are endless taxes in the current system with a few Center levies and government-paid breaks, eliminating this tax burden and reducing the taxpayer’s burden that requires a simplified tax and that is Goods and Services (GST). This paper throws an insight into the Goods and Service Tax concept, need of GST its tax rates.